[Flowers in Lava Rock Near Dettifoss] - Streng, Evelyn Fiedler (1975)
Photograph of flowers in lava rock near Dettifoss. The small, white flowers sit between grey rock alongside green and white grass at the bottom of the photograph. The grey rock is jagged and filled with dark dirt in the cracks where the flowers and grass stand.